What patients and members of their support networks ask about transplant program data. Issue 12 (23rd October 2017) - Schaffhausen, Cory R.; Bruin, Marilyn J.; Chesley, Daryl; McBride, Maureen; Snyder, Jon J.; Kasiske, Bertram L.; Israni, Ajay K.
Abstract: Transplant patients often seek specific data and statistics to inform medical decision making; however, for many relevant measures, patient‐friendly information is not available. Development of patient‐centered resources should be informed by patient needs. This study used qualitative document research methods to review 678 detailed Scientific Registry of Transplant Recipients (SRTR) entries and summary counts of 55 362 United Network for Organ Sharing (UNOS) entries to provide a better understanding of what was asked and what requests were most common. Incoming call and email logs maintained by SRTR and UNOS were reviewed for 2010‐2015. Patients sought a wide range of information about outcomes, waiting times, program volumes, and willingness to perform transplants in candidates with specific diseases or demographics. Patients and members of their support networks requested explanation of complex information, such as actual‐vs‐expected outcomes, and of general transplant processes, such as registering on the waiting list or becoming a living donor. They sought transplant program data from SRTR and UNOS, but encountered gaps in the information they wanted and occasionally struggled to interpret some data. These findings were used to identify potential gaps in providing program‐specific data and to enhance the SRTR website (www.srtr.org ) with more patient‐friendly information.